Interview with Luigi Ferrajoli: Considerations on Constitutionalism - Dyer Cruzado, Edward (2014)
In this inter view, Ferrajoli explains the positivization of constitutionalism and its relationship to the concept of morality and the role of contemporary democracies. He also discusses the issue of freedom of information relating to property rights, to economic initiative and freedom of expression. Finally, the author refers to the insufficiency of the proportionality test as a tool to resolve conflicts between fundamental rights with constitutional recognition.